STRATEGY DIRECTORATE GENERAL OF TAXES ON THE IMPLEMENTATION OF GOOD GOVERNANCE TO IMPROVE THE MOTIVATION AND TAXPAYERS COMPLIANCE - Astini Y.; Utama M.S. (Russian Journal of Agricultural and Socio-Economic Sciences, 2020)
The role of taxes is very vital to date in efforts to improve people's welfare. The decrease in the achievement of tax revenue deserves attention, especially during the Covid-19 pandemic. One of the strategies implemented by the Directorate General of Taxes is to increase taxpayer motivation and compliance through the implementation of good governance. This study is intended to explore the implementation of good governance conducted by the Directorate General of Taxes to increase motivation and taxpayer compliance by using secondary data and a descriptive approach. The results of the study conclude that the implementation of good governance is carried out by the Directorate General of Taxes by providing excellent public services; provide counseling, services, and effective public relations; conduct inspections and effective billing; conduct effective law enforcement; improve the quality of human resources, and maintain the reliability of the Information Management System.